Analgesic Efficacy Evaluation of Ethanol Extract from African Leaves (Vernonia amygdalina Del.) in Acetic Acid-Induced Mice (Mus musculus) - Parmadi, Anom; Rejeki, Sri; Endrawati, Susi; Julianingrum, Poppy (Photon: Jurnal Sain dan Kesehatan, 2024)
African leaves (Vernonia amygdalina Del.) contain many chemical compounds such as tannins, flavonoids, luteolin, coumarins, phenolic acids, lignans, xanthones, anthraquinones, edotides (peptides). African leaves have anti-parasitic, anti-malarial, anti-helminthic, anti-cancer, anticoagulant, analgesic, antipyretic, anti-inflammatory, antioxidant, antidiabetic effects. Tannins are substances in African leaves (Vernonia amygdalina Del.) which are capable of causing analgesic effects. In this study, ethanol extract of African leaves was made where the treatment in the group of test animals was differentiated into doses of 100 mg/kgBW, 200 mg/kgBW, 400 mg/kgBW with a positive control in the form of aspirin and a negative control in the form of cooking oil. The results showed that the percentage of analgesic power for the positive control was 87.42%, the dose of ethanol extract of African Leaf 100 mg/kgBW = 52.27%, 200 mg/kgBW = 62.29%, and a dose of 400 mg/kgBW = 81.50 %.